2019
DOI: 10.1134/s2079970519010076
|View full text |Cite
|
Sign up to set email alerts
|

Regional Capitals of Russia and Their Suburbs: Specifics of the Migration Balance

Abstract: Regional capitals and their suburbs are a few stable points of population increase in Russia. The article singles out the near-capital areas for 72 regional centers of Russia (except for Moscow and Leningrad oblasts, as well as a number of other federal subjects) on the basis of proximity to regional centers. Indicators of migration population increase (decrease) for 2012-2016 were used for their characteristics, calculated from Municipal Units Database indicators both in whole and in part, with division of (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…We also found that in Russia, as in other developed countries (Morrill 1995;Kulu 2008;Vobecka 2010;Johnson/Winkler 2015), families with children tend to move to the suburbs of regional centres. This type of migration can be clearly observed in the Moscow suburbs, and emerges in other parts of the country (Mkrtchyan 2019). But migration from large city centres is still low, in contrast to the countries of western Europe.…”
Section: Discussionmentioning
confidence: 90%
“…We also found that in Russia, as in other developed countries (Morrill 1995;Kulu 2008;Vobecka 2010;Johnson/Winkler 2015), families with children tend to move to the suburbs of regional centres. This type of migration can be clearly observed in the Moscow suburbs, and emerges in other parts of the country (Mkrtchyan 2019). But migration from large city centres is still low, in contrast to the countries of western Europe.…”
Section: Discussionmentioning
confidence: 90%
“…In the southern regions, to increase the activity and attractiveness of densely populated rural areas, a city with a population of 250000 and even 500000 (as a rule, the capital of region) is needed. Such strong differences in the dynamics of the rural population, its settlement pattern, and the specifics of its age structure as young people in depopulating areas depart (Karachurina and Mkrtchyan, 2016;Mkrtchyan, 2019) cannot but affect the nature of human capital and standard of living of the rural population. However, although the population is decreasing in many districts, even the official unemployment rate in rural areas (with very poor registration of rural residents) is higher than in cities, since with the modern transformation of the rural economy, enterprises require fewer employees (Nefedova, 2017;Shagaida and Uzun, 2019 ).…”
Section: Rural Social Spacementioning
confidence: 99%
“…They (Glaeser, 2011; Scott, 2012; Vlahov and Galea, 2002; Laha and Arambagh 2019) emphasized the centripetal force of the city due to global urbanization, population growth, employment and culture, and excellent infrastructure. Conversely, others (Kahn, 2022; Siemiatycki et al, 2020; Al-Kodmany, 2018; Hesse and Siedentop, 2018; Mkrtchyan, 2019) argued for the centripetal force of the city for reasons such as the price of affordable housing, clean environment, and remote work. The COVID-19 pandemic has instigated a tremendous social disaster, resulting in the recognition of a significant urban problem.…”
Section: Introductionmentioning
confidence: 99%